O agronegócio no material didático de ciências da natureza do ensino fundamental I e sua relação com a educação ambiental - Alves, Gisane Salustiano Torigoe [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Environmental Education has been playing an increasingly transformative role in society, seeking to raise awareness about the responsibility of individuals in promoting sustainable development. To this end, it is essential to reflect on how Environmental Education is presented and discussed in school materials in order to become effective in schools. In this context, the objective of this research is to analyze how agribusiness content is addressed in the Natural Sciences teaching material used for Elementary School I in the municipal schools of Tupã and its relationship with the environmental education content. The methodological approach is qualitative and used the Natural Sciences teaching material used by the municipality of Tupã for Elementary School I as the object of analysis. The research is characterized as documentary and bibliographical; the data were studied using Bardin's content analysis, through which the results showed deficiencies in the approach to content relevant to Environmental Education and the decontextualized perspective when addressing content relevant to agribusiness. It is hoped that this research will provide support for discussing the impacts of agribusiness on the environment, in curricular terms, in a more critical manner and that the content producers of this material, as well as other teaching materials, can also use the reflections provided by this research, in order to review the material including deficient approaches and/or correct perspectives presented without the necessary critical reflection.

A Educação Ambiental vem assumindo um papel cada vez mais transformador na sociedade, ao buscar a conscientização sobre a responsabilidade dos indivíduos na promoção do desenvolvimento sustentável. Para tanto reflete-se para que a Educação Ambiental se torne efetiva no ambiente escolar o modo como essa é apresentada e discutida no livro escolar torna-se fundamental. Nesse contexto, o objetivo desta pesquisa é analisar de que modo é abordado o conteúdo de agronegócio no material didático de Ciências da Natureza utilizado para o Ensino Fundamental I nas escolas municipais de Tupã e sua relação com o conteúdo de educação ambiental. A abordagem metodológica é qualitativa e utilizou o material didático de Ciências da Natureza utilizado pelo município de Tupã para o ensino Fundamental I como objeto de análise. A pesquisa se caracteriza como documental e bibliográfica, os dados foram estudados pela análise de conteúdo de Bardin, por meio da qual os resultados mostraram deficiência na abordagem dos conteúdos pertinentes à Educação ambiental e a perspectiva descontextualizada ao abordar conteúdos pertinentes ao agronegócio. Espera-se que esta pesquisa ofereça subsídios para se discutir os impactos do agronegócio sobre o meio ambiente, em termos curriculares, de modo mais crítico e que os produtores de conteúdo deste material assim como de outros materiais didáticos, possam também utilizar as reflexões propiciadas por esta pesquisa, no sentido de rever o material incluindo abordagens deficitárias e/ou corrigir perspectivas apresentadas sem uma reflexão crítica necessária.
Agribusiness in the natural Sciences teaching material for elementary school I and its relationship with environmental education
Keywords: Livro didático; educação ambiental; agronegócio